Avaliação de crianças com indicadores de risco para deficiência auditiva e adesão em um serviço de referência em triagem auditiva neonatal - Ana Luiza de Freitas Rezende (2017)
Introduction: Hearing is extremely important for the global development of children and to detect hearing changes, Newborn Hearing Screening is opportunely used. When the child failed the retest is done to confirm the result and on six moth the follow up is done to auditory monitoring. Objectives: To evaluate the hearing of children with risk indicators for hearing loss who underwent the newborn hearing screening and returned to follow up after six months; To verify the occurrence and types of hearing loss; To verify the correlation of hearing loss with the risk indicators for hearing loss in children who had followed up by a Newborn Hearing Screening Reference Service; To verify if the service is within the specified quality indicators of the Newborn Hearing Screening services. Methodology: This is a longitudinal study in which children with risk indicators for hearing loss that was born at the Universitary hospital had done new born hearing screening. When they obtained "failed" results they were for warded for a new test in one month after the newborn hearing screening, and when they obtained "pass" result they were fowarded for follow-up six months after the newborn hearing screening. In the first stage the children were submitted to Transien Otoacoustic Emissions, Automated Auditory Brainstem Response and Cocleopalpebral Reflex. In addition to the procedures mentioned above, Otoacoustic Emissions by Distortion Product and Immittanciometry were performed, when necessary. Those responsible for the children who did not attend the evaluation, answered a questionnaire to identify the reasons for the evasion. Statistical analysis was performed using the Chi-square test or Fisher's exact test to evaluate the correlation of the categorical variables and the T or Mann-Whitney test to evaluate the correlation of the continuous variables. Results: The results were presented as an article. During the study period, 179 children were screened and 47 children "failed"; There was an association between the "failure" result and the IRDA syndrome and cytomegalovirus, at this stage. In the retest, 20 children "passed", 2hadconductivehearinglossand 25 did not attend; There was association of the "failure" result and the IRDA underweight in this step. 158 children were for warded for follow-up, in which 10 presented conductive hearing loss, 2didnotobtain a conclusive result, 69 presented a "passing" result and 77 did not attend. The no-show of children with lower number of IRDA (1-4 indicators) was higher when compared to children with more IRDA (5-8 indicators). Conclusion: The evaluated children presented only conductive auditory alterations and evaluation that allows to verify such alterations could be part of the screening protocol. Any children were diagnosed with sensorineural hearing loss at six months, which high lights the importance of hearing monitoring in children of older ages in an attempt to diagnose progressive or delayed hearing loss in this population in a timely manner. The high evasion rate is the biggest obstacle to the effectiveness of the Neonatal Hearing Screening service and health promotion strategies aimed at lowering this rate should be performed.